Navigating immune cell immunometabolism after liver transplantation. (April 2021) - Zhang, Wenhui; Liu, Zhikun; Xu, Xiao
Graphical abstract: Highlights: Metabolic programming ultimately affects immune cells activation status and their functional differentiation to further affect post-transplant complications. Targeting regulation signaling and metabolites induce immune tolerance by innate and adaptive immune cells. Targeting immunometabolism is a novel therapeutic approach to induce immune tolerance and prevent post-transplant complications after transplantation. Abstract: Liver transplantation (LT) is the most effective treatment for end-stage liver diseases. The immunometabolism microenvironment undergoes massive changes at the interface of immune functionalities and metabolic regulations after LT. These changes considerably modify post-transplant complications, and immune cells play an influential role in the hepatic immunometabolism microenvironment after LT. Therefore, adequate studies on the complex pathobiology of immune cells are critical to prevent post-transplant complications, and the interplay between cellular metabolism and immune function is evident. Furthermore, immune cells perform their specified functions, such as activation or differentiation, accompanied by alterations in metabolic pathways, such as metabolic reprogramming. This transformation remarkably affects post-transplant complications like rejection. By targeting different metabolic pathways, regulations of metabolism are employed to shape immune responses. These differences of metabolic pathways allow for selective regulation of immune responses to further develop effective therapies that prevent graft loss after LT. This review examines immune cells in the hepatic immunometabolism microenvironment after LT, summarizes possible mechanisms and potential prevention on rejection to acquire immune tolerance, and offers some insight into references for scientific research along with clinical treatment.